Diagnóstico del consumo de alcohol en estudiantes universitarios y su incidencia en la migración académica: Diagnosis of alcohol consumption in university students and its incidence in academic migration (La U Investiga, 2020)
Alcohol consumption spreads as a public health problem in vulnerable groups such as adolescents and young people, in our case study, university students and taking into account the psychosocial problem, the main objective of this research is to identify the percentage rates of consumption and their incidence on academic migration, applying diagnostic and descriptive research with a qualitative approach, as a tool,the ALCOHOL USE DISORDERS IDENTIFICATION TEST (AUDIT) was applied in a population sample of 370 students (175 men and 195 women) of between 18 and 27 years, where the influence of academic migration as part of the causes of alcohol consumption is discussed. In conclusion and as a result, it was found that the majority of students who present a low-risk consumption maintain their residence in the city of origin, however, there is also a considerable group of male students who live outside their hometown. city of origin and present a possible consumption, problem or dependence that denotes a possible greater consumption of alcohol when moving away from the family nucleus, understood as their place of birth.
Keywords: Alcoholism; academic migration; prevention; mental health; AUDIT